IMPROVING STUDENTS’ UNDERSTANDING of CONDITIONAL SENTENCES TYPE 3 USING VOCABULARY SUBSTITUTION DRILL - DIAN KUSUMAWARDANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Grammar is important in language learning in order to form communicative sentences or paragraphs. For school students, grammar means doing the analytical and terminological study of sentences. Conditional if, based on the K13 syllabus, is one of the grammar materials that must be studied and understood by both junior high and high school students. Several factors hindering the teaching and learning process of this material are that students still do not have a vocabulary rich enough to be able to make sentences in English B. Students still do not memorize the forms V1, V2, V3, students do not know the role and function of these words in the structure. sentences, students do not understand basic patterns, lack of reading English media, and students feel bored and bored because the teacher's techniques in teaching grammar are not in accordance with the material to stimulate students' creativity so that students are interested and feel happy in learning conditional if type 3 in class . This research is a classroom action research which consists of four stages, namely planning, action, observation, and reflection with data collection methods in the form of observation, interviews, field notes, pretest and post test, then the results are analyzed using qualitative descriptive techniques. It can be concluded that using a vocabulary substitution drill for conditional if material can improve student learning outcomes in class XII IPA 5 at SMAN 2 Cikarang Utara, seen from student learning outcomes that have increased significantly from each cycle and there is also an increase in the number of students who complete mastery by 34 students. students or be 94% of the total number of students in the class. ABSTRAKTata bahasa (grammar) penting dalam pembelajaran Bahasa agar bisa membentuk kalimat atau paragraf yang komunikatif. Bagi siswa sekolah, grammar berarti melakukan studi analitis dan terminologis kalimat. Conditional if, berdasarkan silabus K13 adalah salah satu dari materi grammar yang harus dipelajari dan dipaham oleh siswa baik SMP maupun SMA. Beberapa faktor hambatan proses belajar mengajar materi ini adalah siswa masih belum memiliki kosa kata yang cukup kaya untuk bisa membuat kalimat dalam B. Inggris, siswa masih belum hafal bentuk V1, V2, V3, siswa tidak mengetahui peran dan fungsi kata-kata tersebut dalam struktur kalimat, siswa belum memahami pola dasar, kurangnya membaca media yang berbahasa Inggris, dan siswa merasa bosan dan bosan karena teknik guru dalam mengajarkan grammar yang tidak sesuai dengan materi untuk merangsang kreativitas siswa agar siswa tertarik dan merasa senang dalam pembelajaran conditional if type 3 di kelas. Penelitian ini adalah penelitian tindakan kelas yang terdiri atas empat tahap, yaitu perencanaan, tindakan, observasi, dan refleksi dengan metode pengumpulan data berupa observasi, wawancara, catatan lapangan, pretest dan post test yang kemudian hasilnya dianalisis menggunakan teknik deskriptif kualitatif. Dapat disimpulkan bahwa dengan menggunakan vocabulary substitution drill untuk materi conditional if dapat meningkatkan hasil belajar siswa kelas XII IPA 5 SMAN 2 Cikarang Utara, dilihat dari hasil belajar siswa yang mengalami peningkatan signifikan dari setiap siklusnya dan juga terdapat peningkatan jumlah siswa yang memenuhi ketuntasan sejumalh 34 orang siswa atau menjadi 94% dari jumlah total siswa kelas.